How much can families afford to pay for college? - Peter L. Hinrichs (W.E. Upjohn Institute for Employment Research, 2025)
This paper studies families' capacity to pay for college in the United States, focusing on changes over time and differences by race and socioeconomic status. I use data from the National Postsecondary Student Aid Study (NPSAS) to document changes over time in the Expected Family Contribution (EFC) from the Free Application for Federal Student Aid (FAFSA). The results suggest that the EFC has been rising over time, and that this has been driven primarily by families in the upper quartile of the income distribution. I then use data from the Panel Study of Income Dynamics (PSID) to calculate alternative measures of the ability to pay for college. I find that it is possible to alter the distribution of who pays what amount by changing details of the EFC calculation, but the extent of this depends on details of the implementation.
Keywords: I22; I23; G51; 330; higher education; affordability; college savings